Comparison of nighttime measurement schedules using a wrist‐type nocturnal home blood pressure monitoring device. Issue 6 (16th March 2021) - Tomitani, Naoko; Kanegae, Hiroshi; Kario, Kazuomi
Abstract: We investigated the optimal nighttime home blood pressure (BP) measurement schedule for wrist BP monitoring. Fifty hypertensive patients (mean age 68.9 ± 11.3 years) self‐measured their nighttime BP hourly using a wrist‐type nocturnal home BP monitoring device at home on two consecutive nights. Using the average 7.2 ± 1.5 measurements per night, we compared the clock‐based index (average of three measurements at 2:00, 3:00, and 4:00 a.m.) and the bedtime‐based index (average of three measurements at 2, 3, and 4 h after bedtime). The clock‐based average was significantly higher than the bedtime‐based average for both systolic BP (2.7 ± 8.2 mmHg, P = .002) and diastolic BP (1.9 ± 5.1 mmHg, P < .001). Compared to the average of all measurements throughout a night (the same definition of ambulatory BP monitoring, ie, from the time point of going to bed to awakening), the clock‐based average was comparable (systolic/diastolic BP: −0.5 ± 5.5/−0.2 ± 3.7), whereas the bedtime‐based average was significantly lower (−3.3 ± 5.0/−2.1 ± 3.6). Thus, the repeated measurement of wrist‐measured nighttime BP at three clock‐based time points per night provided reliable values. Further prospective studies of larger populations are required to confirm the optimal nighttime BP measurement schedule for wrist BP monitoring for the prediction of cardiovascular events.